Anti-discrimination law and the European Union - Bell, Mark (O.U.P. OxfordGB, 2002)
Seeks to provide a better understanding of the forces influencing the direction and development of European social policy, through an analysis of the situation within anti-discrimination law. Takes two specific grounds of discrimination viz. race and sexual orientation and examines their development within EU law and policy.